Cloning, expression pattern analysis, and vector construction of the BvNAC40 gene in sugar beet - FAN Ziqi; SUN Yaqing; LI Ningning; ZHANG Shaoying; LI Guolong (Xibei zhiwu xuebao)
[Objective] NAC transcription factors play a significant role in plant resistance to abiotic stress. In this study, the NAC transcription factor gene BvNAC40 was cloned from the drought-resistant sugar beet variety ‘HI0466’, and its protein structure and expression under drought stress were analyzed. This research provided a theoretical basis for further analysis of BvNAC40 and the breeding of drought-resistant sugar beet varieties. [Methods] BvNAC40 gene was cloned using the PCR method, and its protein structure was analyzed by bioinformatics methods. Subcellular localization was observed with green fluorescent protein (GFP). Expression of BvNAC40 under drought stress was analyzed by qRT-PCR. Overexpression vectors and virus-induced gene silencing (VIGS) vectors for BvNAC40 were constructed using homologous recombination. [Results] The CDS of BvNAC40 was 1 182 bp long, encoding 393 amino acids, which was classified within the NAC transcription factor family, with a transmembrane domain at the C-terminus. Subcellular localization showed that it was primarily located in the nucleus. Under drought stress, BvNAC40 expression was upregulated in both the leaves and roots of sugar beets. [Conclusion] The BvNAC40 gene is specifically expressed in response to drought stress in sugar beets, laying the foundation for future studies using transgenic technology.